Hubungan frekuensi menyikat gigi dengan tingkat kebersihan gigi dan mulut siswa sekolah dasar negeri di kecamatan Palaran kotamadya Samarinda provinsi Kalimantan Timur - Silvia Anitasari; Nina Endang Rahayu (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2005)
The aim of this study was to get information about the relation of frequency of teeth brush to oral hygiene of elementary school children in Palaran Samarinda. The samples were 1650 first to sixth grade elementary school children taken from 10 state elementary schools at Palaran Samarinda. Oral hygiene was measured by OHI-S index, and frequency of teeth brush was measured by questionnaire. Statistical analysis was performed with chi-square test. The results showed that 6.73% have good oral hygiene, 59.03 % moderate and 34.24% poor. The frequency of teeth brush showed that 18% at 1x, 34.24 % at 2x, 61.88 % at 3x; 1.70% at 4x. With statistical analysis showed that there were relation of frequency of teeth brush to oral hygiene school children (X2 = 98.5, df = 6 and p = 12.59. This study concluded that oral health knowledge and exercise become successful in children from state elementary school at Palaran.